Graffiti work at Mazagaon - Mumbai Archive Project Team (Jio Institute, 2024)
There are multiple stories regarding the origin of Mazagon’s name. The popularly accepted story suggests it came from Matsyagrama (a fishermen’s village), which in the local language became Machch-gav. The English referred to it as Massegoung, which was shortened to Mazagaon, while the Portuguese called it Mazaguao. Another simpler theory states that it originated from the Marathi phrase ‘maza gaon,’ which means ‘my own village.’